Effect of 940 nm Gallium Arsenide Laser on dental hard tissues temperature propagation - Javier Higuera; Ariel Denis Espinoza; Sebastian Contreras Marino (Brazilian Dental Science)
Despite the extensive literature available on laser at the present, there are few articles about the temperature of laser radiation and its propagation on dental hard tissues. The present study general objective is to evaluate in vitro the effect of temperature increase produced by the laser radiation of 940 nm on the dental hard tissues and, as specific objectives a) analyze current parameters using 940 nm laser on dental hard tissues b) assess the most appropriate criteria for this wavelength on dental hard tissues. 4 groups of 5 teeth each (lower incisors, upper incisors, canines and molars) were irradiated with 6 powers and frequencies (0.1 to 0.4W, in continuous or pulsed mode). The results of this study allow us to ensure that, in the chosen parameters, major powers, but delivered in pulsed manner, generate less temperature rise. Extremely significant differences were found between groups of lower incisors and molars. 0.1W power, pulsed mode for 20 msec, with 20 millisecond intervals, generated less than 4 Celsius degrees of temperature increase in all the cases studied. In conclusion, the use of powers of up to 0.4W, in pulsed mode, generated thermal effects of less than 4 Celsius degrees.